Współczesne tendencje zmian w tradycyjnym podejściu do organizacji pracy - Mikołajczyk, Zofia (Contemporary tendencies of changes in the traditional approach to organization ofw work, 2005)
Classical rules of organizing and rationalizing work referred to manual and mechanized production and office processes, mainly in the closed area of companies and their basic elements: methods, time and posts of work. The unprecedented - in the history of mankind - progress of electronic technology and modem tools of information processing and communication at the end of the 20th century and the beginning of the 21st century enabled their fast implementation in practice. This created conditions for mobility and flexibility of the performance of some types of professional work outside the permanent place (company) and at the time unlimited by its beginning and end. Therefore a chance arose to develop a new, different from traditional assumptions, form of organizing work from a distance, which is called telework. The article presents the basic types of telework and an example of their use in British practice, based on the results of the research carried out in 2002 by the London Institute for Employment Studies. Positive and negative aspects of this form of organization of work for companies management and their employees are discussed briefly. Finally the situation in this domain in Poland in the first years of this century is outlined.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 602-611